2006
DOI: 10.1088/0953-8984/18/30/s08
|View full text |Cite
|
Sign up to set email alerts
|

Photon stimulated desorption of hydrogen from diamond surfaces via core-level excitations: fundamental processes and applications to surface studies

Abstract: In this paper we review a number of works on photon stimulated ion desorption (PSID) of hydrogen from various diamond surfaces. In particular, we elaborate on the bonding configuration of adsorbed hydrogen (deuterium) and its neighbouring atoms, and its thermal stability in surface and sub-surface regions. Usage of hydrogen PSID as a characterization method involves detailed description of the mechanism and dynamics of hydrogen ion desorption initiated by a synchrotron generated photon beam. Several compliment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…This effect was hinted at in an experiment involving the photon-stimulated desorption of H + and H − ions from hydrogen-terminated diamond surfaces. 75 The experimental results suggested that H − ions were released via an indirect mechanism involving secondary electrons as an intermediary versus H + ions which were produced via a direct mechanism related to the core excitation, both consistent with the eFF simulation results.…”
Section: B Auger Relaxation In Core-ionized Diamondoidssupporting
confidence: 81%
“…This effect was hinted at in an experiment involving the photon-stimulated desorption of H + and H − ions from hydrogen-terminated diamond surfaces. 75 The experimental results suggested that H − ions were released via an indirect mechanism involving secondary electrons as an intermediary versus H + ions which were produced via a direct mechanism related to the core excitation, both consistent with the eFF simulation results.…”
Section: B Auger Relaxation In Core-ionized Diamondoidssupporting
confidence: 81%
“…We find that, in the direct Auger process, nonionized but excited electrons play a key role in causing carbon-hydrogen and carbon-carbon bonds to break. In addition, we discover with eFF a previously unknown minor pathway for proton desorption involving electron impact ionization, which may explain the doubly peaked kinetic energy distribution for ejected protons observed experimentally (14).…”
Section: Discussionmentioning
confidence: 60%
“…Experimentally, it has been observed that protons produced via photon-stimulated desorption (PSD) on hydrogenated diamond are emitted with a doubly peaked kinetic energy distribution (14). We interpret these two classes of protons as originating from direct Auger versus secondary impact pathways, with direct Auger protons ejected more slowly because of the presence of electrons that linger in the bond over the core hole lifetime.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This could be due to the decrease in the CÀ H functionalization of the surface. [23] The Fe 2p XAS spectra for the SWCNT samples are shown in Figure 4B. In the L 3 -edge, the observed peak at lower energy arises from metallic Fe, whereas the higher peak comes from oxidized Fe.…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%